EFFECT OF INDUSTRY-BASED LEARNING AND MOTIVATION ON STUDENT'S ENTREPRENEURSHIP COMPETENCIES - Handayani, Farida Hanim; Rufii, Rufii; Harwanto, Harwanto (EDUTECH, 2020)
This study aims to analyze: 1) entrepreneurial competence differences between students who are guided by using the concept of industry-based learning (Teaching Factory) and groups of students who are guided by using conventional learning concepts, 2) differences between students who have high learning motivation and students who have low learning motivation towards their entrepreneurial competencies, and 3) significance of interactions between industry-based learning (Teaching Factory), conventional learning, and learning motivation towards entrepreneurial competencies. The research method used was the experimental method with a factorial 2x2 design. The data collection in this study used questionnaire, written tests, and practice tests. The collected data were then analyzed by using the two-way ANOVA. The results showed that: 1) there were significant differences entrepreneurial competencies of students in the learning models, 2) there were significant differences in the students 'learning motivation towards their entrepreneurial competencies, 3) there were interactions between industry-based (Teaching Factory) and conventional learning models and learners' motivation towards entrepreneurial competencies.Â Penelitian ini bertujuan untuk menganalisis: 1) perbedaan kompetensi kewirausahaan antara siswa yang dibimbing dengan menggunakan konsep pembelajaran berbasis industri (Teaching Factory) dan kelompok siswa yang dibimbing dengan menggunakan konsep pembelajaran konvensional, 2) perbedaan siswa yang memiliki motivasi belajar dan siswa yang memiliki motivasi belajar rendah terhadap kompetensi kewirausahaannya, dan 3) signifikansi interaksi antara pembelajaran berbasis industri (Teaching Factory), pembelajaran konvensional, dan motivasi belajar terhadap kompetensi kewirausahaan. Metode penelitian yang digunakan adalah metode eksperimen dengan desain faktorial 2x2. Pengumpulan data dalam penelitian ini menggunakan angket, tes tertulis, dan tes praktik. Data yang terkumpul kemudian dianalisis dengan menggunakan ANOVA dua arah. Hasil penelitian menunjukkan bahwa: 1) terdapat perbedaan yang signifikan kompetensi kewirausahaan siswa pada model pembelajaran, 2) terdapat perbedaan yang signifikan motivasi belajar siswa terhadap kompetensi kewirausahaannya, 3) terdapat interaksi antara berbasis industri (Teaching Factory) dan model pembelajaran konvensional serta motivasi peserta didik terhadap kompetensi kewirausahaan.